Subjective perceived outcome of subthalamic deep brain stimulation in Parkinson's disease one year after surgery. (March 2016) - Maier, Franziska; Lewis, Catharine J.; Horstkoetter, Nina; Eggers, Carsten; Dembek, Till A.; Visser-Vandewalle, Veerle; Kuhn, Jens; Zurowski, Mateusz; Moro, Elena; Woopen, Christiane; Timmermann, Lars
Abstract: Objectives: Dissatisfaction with subthalamic deep brain stimulation (STN-DBS) despite motor improvements has been observed in Parkinson's disease (PD). Hence, we compared patient's subjective perceived outcome 12 months after surgery (12mFU) with clinical measures to identify risk factors of dissatisfaction. Methods: Patients were examined at baseline and 12mFU. Quality of life (QoL), neuropsychiatric, cognitive and neurological functioning was measured. Patients were classified concerning their subjective outcome (negative = dissatisfaction; mixed; positive = satisfaction) at 12mFU using semi-structured interviews. First, the three groups were compared concerning interview statements. Second, repeated measures ANOVAs with group as between-subjects factor were applied to find significant effects of time, group, or interaction. Third, binary logistic regression determined predictors of dissatisfaction. Results: Of the 28 enrolled patients, 25% perceived their outcome as negative, 32.1% as mixed, and 42.9% as positive. Concerning interview statements, dissatisfied patients mentioned significantly less often improved QoL and reduced medication, and reported worsening of mental state, and social interaction. For the whole sample, significant improvement over time was found for motor functioning, daily dopamine dosages, and QoL. Apathy significantly worsened over time, but dissatisfied patients were overall more apathetic and depressed than the other groups. Significant interaction of group and time was identified for QoL, which only improved in the mixed and satisfied group. Finally, preoperative apathy and axial symptoms predicted dissatisfaction with STN-DBS. Conclusions: Although motor symptoms and QoL improved in the whole sample, 25% of patients showed disappointment with STN-DBS. Especially apathy predicts dissatisfaction and should be considered preoperatively. Highlights: Qualitative and quantitative methods determined subjective perceived outcome one year after STN-DBS surgery. Motor improvement and medication reduction in the whole sample. 25% of PD patients perceive their long-term DBS outcome as negative. Higher preoperative apathy and axial symptoms predict negative perceived outcome.